Electrochemotherapy as a treatment option for feline nasal melanoma. Issue 1 (February 2022) - Little, Annika; Macfarlane, Michael
Case summary: A 4-year-old domestic shorthair cat presented to North Downs Specialist Referrals for treatment of a 7 mm melanoma of the nasal planum. Two treatments of electrochemotherapy using intravenous bleomycin as a chemotherapeutic agent were administered. The tumour was no longer visible after treatment. At the 292-day follow-up there was no recurrence at the site and the patient was clinically well. Relevance and novel information: There are few data concerning the outcomes of cats with non-ocular feline melanomas and there are currently minimal descriptions in the literature of electrochemotherapy as a treatment option. The available data suggest that nasal melanoma may have a worse prognosis, and that melanomas are locally invasive and have a high propensity for metastasis. The current most effective means for local control is surgery with wide margins. Given the location in this case, this would have required nasal planectomy, while electrochemotherapy provided an effective and possibly more attractive alternative.